Effect Of Terapeutic Nurse Communication On The Level Of Satisfaction Patient Care Hospital In The Floor Ii Tour Uit Hospital Makassar - Lahendri - (Jurnal Mirai Management, 2016)
Abstract The purpose of this study are: (1). To know and analyze the effect of verbal communication on of patient satisfaction in the treatment room the second floor RSU roses. UIT Makassar Tourism (2). To know and analyze the impact of nonverbal communication on of patient satisfaction in the treatment room the second floor RSU roses. UIT Travel Makassar (3) To know and analyze the effect of verbal and non verbal communication simultaneously on of patient satisfaction in the treatment room the second floor RSU roses. UIT Travel Makassar, (4) To know and to analyze which of the more influential variables between verbal or nonverbal communication communication of of patient satisfaction in the treatment room the second floor RSU roses. UIT Makassar Tourism.The research method used in this research is survey method with quantitative approach with cross sectional study approach using variables, both as independent variable and dependent variable. The sample used in this research is as much as 80. Data analysis is descriptively quantitative by using SPSS method of Multiple Linear regression analysis.The results based on hypothesis testing to prove that (1). Verbal communication positive and significant impact on of patient satisfaction in the treatment room the second floor RSU roses. UIT namely Makassar travel with a standardized parameter value of 0.409 with a significant value of 0.000. (2). Non Verbal Communication and the most significant positive impact on of patient satisfaction in the treatment room the second floor RSU roses. UIT namely Makassar travel with a standardized parameter values for 0285 with significant value 0.001. Keyword: Therapeutic Communication, Patient Satisfaction